Examining the e-learning attitudes of Indonesian students during the COVID-19 pandemic - Irwanto, Irwanto; Cahyana, Ucu; Ayuni, Ni Putu Sri (Journal of Education and e-Learning Research, 2024)
The COVID-19 epidemic has impacted higher education institutions across the country by switching traditional teaching practices to online learning. The attitudes of students towards e-learning are essential to research in order to determine the extent to which successful implementation of online learning. Thus, this research aims to evaluate the attitudes of Indonesian students towards e-learning throughout the pandemic. The study adopted a quantitative research approach through a survey questionnaire. The attitude of students was evaluated using the attitude scale towards e-learning. The questionnaire comprised 20 items assessing students’ attitudes towards remote learning. A questionnaire was distributed to 342 (255 female and 87 male) undergraduate students who took online courses at an Indonesian state university. The statistical analyses including descriptive statistics, t-tests and one-way ANOVA were used in the present study. The results suggested that students’ e-learning attitudes tend to be neutral. The t-test and ANOVA indicated that there was no statistically significant gap in students’ attitudes with respect to gender, daily internet usage time or level of COVID-19. Meanwhile, age, study year and personal computer ownership exerted a statistically significant impact on e-learning attitudes. Teachers can better prepare for the adoption of online learning during COVID-19 and beyond by using the valuable insights provided by the findings.